Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd006108.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for vasomotor menopausal symptoms

Abstract: Main results We included five RCTs (733 women) comparing exercise with no active treatment, exercise with yoga and exercise with HT. The evidence was of low quality: Limitations in study design were noted, along with inconsistency and imprecision. In the comparison of exercise versus no active treatment (three studies, n = 454 women), no evidence was found of a difference between groups in frequency or intensity of vasomotor symptoms (SMD-0.10, 95% CI-0.33 to 0.13, three RCTs, 454 women, I 2 = 30%, low-quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 70 publications
3
34
0
3
Order By: Relevance
“…HRT has ben shown to alleviate such symptoms but as indicated can have serious side effects. Lifestyle modification interventions, including structured exercise and physical activity, have the potential to reduce vasomotor menopausal symptoms [18,44]. In fact, in the longitudinal Melbourne Women's Midlife Health Project, in which 438 women were followed over 8 years, those who exercised every day at baseline were 49% less likely to report hot flashes, and those whose exercise levels decreased were more likely to report hot flashes [45].…”
Section: Benefits To Vasomotor Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…HRT has ben shown to alleviate such symptoms but as indicated can have serious side effects. Lifestyle modification interventions, including structured exercise and physical activity, have the potential to reduce vasomotor menopausal symptoms [18,44]. In fact, in the longitudinal Melbourne Women's Midlife Health Project, in which 438 women were followed over 8 years, those who exercised every day at baseline were 49% less likely to report hot flashes, and those whose exercise levels decreased were more likely to report hot flashes [45].…”
Section: Benefits To Vasomotor Symptomsmentioning
confidence: 99%
“…The type of exercise intervention was analysed amongst 6 eligible studies in the management of vasomotor menopausal symptoms and was compared to HRT [69]. There was insufficient evidence demonstrating that exercise was effective in treating vasomotor menopausal symptoms, and, it was not clear whether exercise was more beneficial compared to HRT or yoga [69].…”
Section: Or Not To Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Regular physical activity has namely been suggested to increase hypothalamic opioid activity and may therefore again stabilize thermoregulation. A number of cross sectional studies and a few intervention studies [78][79][80][81] have since then been reported and most of them suggest but do not prove that regular physical activity may decrease the risk of having vasomotor symptoms or reduce the symptoms. The recent Cochrane review concluded that existing studies provide insufficient evidence that exercise is an effective treatment for vasomotor menopausal symptoms, or whether exercise is more effective than hormone replacement therapy or yoga [81].…”
Section: Physical Activity and Menopausal Hot Flushesmentioning
confidence: 99%
“…A number of cross sectional studies and a few intervention studies [78][79][80][81] have since then been reported and most of them suggest but do not prove that regular physical activity may decrease the risk of having vasomotor symptoms or reduce the symptoms. The recent Cochrane review concluded that existing studies provide insufficient evidence that exercise is an effective treatment for vasomotor menopausal symptoms, or whether exercise is more effective than hormone replacement therapy or yoga [81]. It may be added that the type of activity is probably essential in order to reduce vasomotor instability, at least if the opioid theory will prove to be correct, since strength training including large muscle groups is probably more effective in this respect than e.g.…”
Section: Physical Activity and Menopausal Hot Flushesmentioning
confidence: 99%